Implementasi Green Accounting pada UMKM: Dampak terhadap Keberlanjutan dan Efisiensi Operasional - Sugito Putra, Toufiq Agung Pratomo; Katuruni, Innas Susantira (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study explores the implementation of Green Accounting in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on its impact on environmental sustainability and operational efficiency. Through a systematic literature review, the study analyzes various research related to Green Accounting, sustainable practices in MSMEs, and adoption challenges in developing countries. Findings indicate that Green Accounting enhances MSMEs' financial and environmental performance by reducing environmental costs, fostering green innovation, and improving supply chain collaboration. However, barriers such as limited resources and lack of awareness remain significant challenges. The study concludes that adopting Green Accounting requires government policy support and training for MSMEs, recommending integration with green supply chain management to achieve better operational efficiency